PROBLEM-BASED LEARNING IN BASIC PHYSICS - V - Mody, A. K.; Pradhan, H. C. (SCHOOL SCIENCE, 2014)
In this article, fifth in the series, we present problems on electricity and magnetism. Methodology and philosophy of selecting these problems have already been discussed (Mody and Pradhan 2011). To review the methodology in brief, we note here that this Problem-based Learning (PBL) starts after students have been introduced to formal structure of physics. Ideally students would attempt only main problem. If they find it difficult, then depending upon their area of difficulty, right auxiliary problem have to be introduced by teacher who is expected to be a constructivist facilitator. Teacher may choose as per her/his requirement or may construct questions on the spot to guide student to the right idea and method.